Growing Feijoa Fruit in Florida - Kevin Folta; Dustin Huff; Ali Sarkhosh (EDIS)
Feijoa is often found in central and north Florida landscapes as a durable and cold-hardy plant for hedges and foundation plantings, and as a dooryard fruit. Its value as a potentially heavy producer of flavorful fruits (and flavorful flowers) is frequently overlooked due to issues in pollination and limited genetic improvement. This new 5-page publication of the UF/IFAS Horticultural Sciences Department describes the opportunity and limitations of feijoa as a horticultural crop. https://edis.ifas.ufl.edu/hs1424